Genomic Analysis Reveals Human-Mediated Introgression From European Commercial Pigs to Henan Indigenous Pigs - Wang, Kejun; Zhang, Lige; Duan, Dongdong; Qiao, Ruimin; Li, Xiuling; Li, Xinjian; Han, Xuelei (Frontiers in Genetics, 2021)
Introgression of genetic features from European pigs into Chinese pigs was reported possibly contributing to improvements in productivity traits, such as feed conversion efficiency and body size. However, the genomic differences from European pigs and the potential role of introgression in Henan indigenous pigs remains unclear. In this study, we found significant introgression from European pigs into the genome of Chinese indigenous pigs, especially in Henan indigenous pigs. The introgression in Henan indigenous pigs, particularly in the Nanyang black pig, was mainly derived from Duroc pigs. Most importantly, we found that the NR6A1, GPD2, and CSRNP3 genes were introgressed and reshaped by artificial selection, and these may have contributed to increases in pig body size and feed conversion efficiency. Our results suggest that human-mediated introgression and selection have reshaped the genome of Henan pigs and improved several of their desired traits. These findings contribute to our understanding of the history of Henan indigenous pigs and provide insights into the genetic mechanisms affecting economically important traits in pig populations.